2011
DOI: 10.1038/ismej.2011.191
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and complex bacterial profiles in human periodontitis and health revealed by 16S pyrosequencing

Abstract: Periodontitis has a polymicrobial etiology within the framework of a complex microbial ecosystem. With advances in sequencing technologies, comprehensive studies to elucidate bacterial community differences have recently become possible. We used 454 sequencing of 16S rRNA genes to compare subgingival bacterial communities from 29 periodontally healthy controls and 29 subjects with chronic periodontitis. Amplicons from both the V1-2 and V4 regions of the 16S gene were sequenced, yielding 1 393 579 sequences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

120
951
14
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 819 publications
(1,108 citation statements)
references
References 20 publications
120
951
14
7
Order By: Relevance
“…2B). This separation according to clinical phenotype was also observed when data sets reported by the HMP (healthy subjects only), Abusleme et al (31), and Griffen et al (30) (both healthy and periodontitis groups) were included in the analysis (Fig. 2C to G).…”
Section: Microbial Community Structuresupporting
confidence: 72%
See 4 more Smart Citations
“…2B). This separation according to clinical phenotype was also observed when data sets reported by the HMP (healthy subjects only), Abusleme et al (31), and Griffen et al (30) (both healthy and periodontitis groups) were included in the analysis (Fig. 2C to G).…”
Section: Microbial Community Structuresupporting
confidence: 72%
“…Raw sequencing reads were obtained from three other studies: the HMP (42), Griffen et al (30), and Abusleme et al (31). The reads were downloaded from the HMP DACC website and the Sequence Read Archive (SRA) (SRA accession number SRP009299 for data reported by Griffen et al and SRA accession number SRP012422 for data reported by Abusleme et al).…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations